Surgical Management of Acute Cholecystitis: Early versus Delayed Laparoscopic Cholecystectomy - M Fadillah Tarigan (Universitas Methodist Indonesia, 2025)
Acute cholecystitis is a common surgical emergency, primarily caused by gallstones blocking the cystic duct. Even though laparoscopic cholecystectomy is universally regarded as the best treatment, the best time for surgery is still a matter of clinical and logistical concern. This narrative review assesses the existing evidence about early versus delayed laparoscopic cholecystectomy. Evidence from studies and guidelines consistently demonstrates suggesting early laparoscopic cholecystectomy yields superior results, including reduced total length of hospital stay and lower rates of recurrent biliary events, without increasing major morbidity, conversion to open surgery, or bile duct injury when conducted in accordance with safe surgical principles. Delayed laparoscopic cholecystectomy is still an option for some patients who are temporarily unsuitable for surgery, have uncontrolled sepsis, need their gallbladder drained, or can't get to the right surgical expert. Consequently, the time of intervention ought to be tailored to the patient's physiology, disease severity, and institutional capacity, rather than conforming to a predetermined temporal threshold. Early laparoscopic cholecystectomy needs to be considered the standard of treatment wherever possible, whereas delayed cholecystectomy management should be confined to meticulously chosen cases. Keywords: acute cholecystitis; laparoscopic cholecystectomy; early cholecystectomy; delayed cholecystectomy; gallbladder